Comparison of Outcome among patients undergoing Vesicovaginal Fistula Repair through Transabdominal approach with and without Interposition Omental Flap (Journal of Fatima Jinnah Medical University, 2024)
Background: Vesicovaginal fistula (VVF) is an abnormal connection between the bladder and vagina, causing urinary incontinence. It often results from surgical injury or malignancy. Interposition flaps, including the omentum flap in trans-abdominal repairs, help close the defect and improve outcomes.Objective: To compare the outcome among patients undergoing vesicovaginal fistula repair through transabdominal approach with and without interposition omental flap.Patients and Methods: A randomized controlled trial was conducted from July 2021 to January 2022 at the Urology Department, Sir Ganga Ram Hospital, involving 44 patients with supratrigonal vesicovaginal fistulas (VVF) ≤2 cm and ≤2 openings. Patients with malignancy, radiotherapy, recurrent or infratrigonal VVF, ureterovaginal fistula, or localized infection were excluded. The experimental group underwent VVF repair with an interposition omental flap, while the control group underwent repair without the flap. SPSS version 24 was used for data analysis. The comparison between groups for proportions of fistulous openings, peri-operative complications and treatment success by chi-square test. P-value of ≤0.05 was considered as significantResults: The experimental group (mean age 36.5 ± 7.4 years) and control group (mean age 39.1 ± 10.1 years) showed similar peri-operative wound infection rates (9.1%). Complications in the experimental group included bleeding (9.1%), bowel perforation (4.5%), and higher fistula recurrence (22.7% vs. 18.2%). Treatment success at 2 weeks was 81.8% with the graft and 90.9% without it.Conclusion: In conclusion, using an interposition graft in VVF repair did not significantly improve success rates or reduce morbidity compared to repairs without a graft.
Keywords: vesicovaginal fistula; Omental Flap; Urology; trans-abdominal approach